Guía didáctica basado en el ABP, para el aprendizaje de biología en tercer año de bachillerato en el instituto tecnológico superior “cinco de junio” de la ciudad de quito, provincia de pichincha, durante el período lectivo marzo-julio de 2016. - Santiago Chucho, Geovanny Iván (2016)
Teaching Guide based on ABP, to promote learning of Biology born from the need for an educational resource that promotes learning participation of students in third year of high school and overcome the verbal transition of knowledge from teacher to the student to promote interest and motivation of the learner to learning from collaborative work, the development of thought or autonomous, teachers are forced to innovate the educational task for students to learn to learn under the pedagogical constructivism. Research is conducted in the Third Year Bachelor of Technology Institute Superior "Cinco de Junio" of the city of Quito, Pichincha province, during the school period from March to July 2016. The research design used is correlational kind of research is cuasiexperimental, population and sample consisted of 68 students, a manager and two teachers. The techniques of collecting information that was used is the survey indicators Based Learning and interview to validate the guide with teachers working in the field of biology. After applying a guide the strengths that the educational guide both the development of the educational process and the activities planned for students to perform their cognitive process through working groups, situations, problems and analysis, reflection, synthesis is identified and their autonomous learning, the suggestions made by the students as well, given the ease of use, it is recommended to use this educational resource that is based on the Updating and strengthening existing Curricular analyzing Block No. 2, Nucleic acids selecting the contents to adapt to them the issues of the biochemical bases, DNA replication conclusion of the investigation can say it was an enriching experience that has improved professional researcher profile, so the process of learning of Biology third year of high school in the city of Quito